Pelabelan Total Sisi Ajaib Super pada Graf T(2,n,n+6) - Ni Nyoman Ayulita Andayani; I.G.N Pujawan; Made Juniantari (FKIP Universitas Mataram, 2022)
Graph labeling is one of the topics in graph theory which helps a lot in solved everyday problems. Study on labeling on graphs, especially the Super Edge-Magic Total Labelling is still ongoing, although for some classes of graph have been known to have Super Edge-Magic Total Labelling, but many problems that have not been resolved, one of them is the conjecture stated in the paper Enomoto et al (1998: 108 ) that all tree graphs have (super) edge-magic total labeling. Motivated by this conjecture, this study examined the total labeling of the super magical side of Graph T (2, n, n + 6) which is one of the tree graphs. The results of this study is show that Graph T (2, n, n + 6) is a graph that can be labelled by the Super Edge-Magic Total Labeling (SEMT), with the magic value of graph T (2, n, n + 6) for n is even number is k = 5n +23, and for n is even number the magic value is k = 5n +24.